2017
DOI: 10.3390/polym9020066
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Responsive Hydrogel Nanoparticles upon Polyelectrolyte Complexation

Abstract: Characterization of responsive hydrogels and their interaction with other molecules have significantly expanded our understanding of the functional materials. We here report on the response of poly(N-isopropylacrylamide-co-acrylic acid) (pNIPAm-co-AAc) nanogels to the addition of the poly(allylamine hydrochloride) (PAH) in aqueous dispersions. We find that the hydrodynamic radius and stability of nanogels are dependent on the PAH/nanogel stoichiometry. If the nanogel solution is titrated with very small aliquo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 58 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…These phenomena could come from the pH changes and passivation of carboxylate group in the biotinylated nanogels when the neat nanogels underwent EDC coupling step. It has been reported that the size of nanogels in aqueous solution is mostly influenced by charge, cross-linking density, temperature, and pH but not by the addition of mass. Moreover, since biocytin is a small molecule, it is unlikely to be explained by the fact that increase in the size of the biotinylated nanogels is solely contributed by the addition of biocytin.…”
Section: Results and Discussionmentioning
confidence: 99%
“…These phenomena could come from the pH changes and passivation of carboxylate group in the biotinylated nanogels when the neat nanogels underwent EDC coupling step. It has been reported that the size of nanogels in aqueous solution is mostly influenced by charge, cross-linking density, temperature, and pH but not by the addition of mass. Moreover, since biocytin is a small molecule, it is unlikely to be explained by the fact that increase in the size of the biotinylated nanogels is solely contributed by the addition of biocytin.…”
Section: Results and Discussionmentioning
confidence: 99%
“…PNIPAm-co-AAc microgels are responsive to external stimuli such as temperature and pH, resulting in the decrease or increase of the hydrodynamic radius of microgels, as shown in Figure 2a,b. In a previous study, we report that pNIPAm-co-AAc microgels are complexed with poly(allylaminehydrochloride) (PAH) via ion pairing, which shows a decrease or increase of the microgel's hydrodynamic size mainly due to the crosslinking and charge shielding effects [37]. Thus, we hypothesize that pNIPAm-co-AAc microgels are able to form the complex structure with amine-functionalized magnetic nanoparticles (aMNPs) in similar mechanisms, which provides an easy and practical method for preparation of hybrid MNP-microgels, as shown in Figure 2c,d, while retaining the thermoresponsivity.…”
Section: Resultsmentioning
confidence: 99%
“…In the existing literature, PAA nanogels synthesized with radiation, or any other method, are not broadly studied. In general, most of the applications of poly(acrylic acid) in nanogel science focus on copolymers (with other materials such as poly(N-isopropylacrylamide) [46][47][48][49][50]), interpolymer complexes (e.g., with poly(N-vinylpyrrolidone) [30,51] or poly(ethylene oxide) [52]), and hybrid organic-inorganic structures [41,[53][54][55]. Acrylic acid can be also grafted onto other nanoparticles to provide carboxylic groups [29,56], but nanoparticles based solely on PAA are rarely used despite their interesting properties.…”
Section: Introductionmentioning
confidence: 99%